2005
DOI: 10.22358/jafs/67126/2005
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of reproductive traits and egg traits of crossbred geese with Graylag ancestry

Abstract: The aim of this study was to evaluate the reproductive traits and physical traits of the eggs of three-breed crosses of geese -White Kołuda (WK) × Slovakian (Sl) × Graylag (Gr) -in terms of the direction of crossing of the parents, and to determine differences in the chemical composition of eggs at the beginning and at the end of the reproductive period. The highest egg production (37 eggs), egg weight (192.4 g) and body weight (males 7491 g, females 6507 g) were characteristic of the crossbreds Sl'GrWK. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
2
5
2
Order By: Relevance
“…Similar and partly poorer results in mongrels obtained by reciprocal interbreeding of several goose breeds were reported by Mazanowski and Chelmonska (2000), Mazanowski and Adamski (2002), Mazanowski and Bernacki (2006). Poorer and significantly lower egg fertility and hatchability of Italian White Goose and two-breed mongrels is reported by Rosinski (2000) and Ðermanović et al (2008).…”
Section: Data Insupporting
confidence: 75%
See 1 more Smart Citation
“…Similar and partly poorer results in mongrels obtained by reciprocal interbreeding of several goose breeds were reported by Mazanowski and Chelmonska (2000), Mazanowski and Adamski (2002), Mazanowski and Bernacki (2006). Poorer and significantly lower egg fertility and hatchability of Italian White Goose and two-breed mongrels is reported by Rosinski (2000) and Ðermanović et al (2008).…”
Section: Data Insupporting
confidence: 75%
“…Saatci et al (2005) have established in all strains (white, yellow, piebald and black) and Ðermanović et al (2008) in two-breed mongrels, a significantly lower egg mass (under 151 g) than in our study. Depending on the goose mongrel type, Mazanowski and Chelmonska (2000), Mazanowski et al (2002), Mazanowski and Bernacki (2006) reported larger mean egg mass (184 g), but also significantly smaller (148 g) than that reported in our study (168.91 g). Similarly, Razmaitè et al (2014) reported larger (186.69 g -3rd year of breeding), and lower (123.40 g -1st year of breeding) in case of Lithuanian VishtinPs Geese.…”
Section: Data Incontrasting
confidence: 51%
“…Somewhat higher hatchability percentage (81.5 %) was reported by the same authors (2016a), also of the White Koluda geese, but the fertilisation was insignificantly lower than that reported in our study for all weight groups (88.00 %). Similar and somewhat poorer results in pure breeds and mongrels obtained by the reciprocal interbreeding of various goose races (including the Italian White) was reported by Mitrovic et al (2016), Mazanowski and Chelmonska (2000), Mazanowski and Adamski (2002), Mazanowski and Bernacki (2006). Rosiñski (2000) and Ðermanovic et al (2008) report poorer and considerably lower egg fertilisation rate and gosling hatchability of Italian White Goose and tworace mongrels.…”
Section: The Data Insupporting
confidence: 60%
“…Saatci et al (2005) have reported in all goose strains (white, yellow, multicolour and black), and Ðermanovic et al (2008) in two race mongrels, a considerably smaller egg mass (under 151 g) of the Italian White goose than that obtained in our research (the average mass of all incubated eggs was 168.91 g). Depending on the goose mongrels, Mazanowski and Chelmonska (2000), Mazanowski et al (2002), Mazanowski and Bernacki (2006) have reported a larger average egg mass (184 g) than the one established in our study (168.91 g), but also considerably smaller (148 g). Similarly, Razmaite et al (2014) Bednarczyk and Rosiñski (1999).…”
Section: The Data Incontrasting
confidence: 46%
See 1 more Smart Citation